2015
DOI: 10.1371/journal.pgen.1005064
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial Infection Drives the Expression Dynamics of microRNAs and Their isomiRs

Abstract: The optimal coordination of the transcriptional response of host cells to infection is essential for establishing appropriate immunological outcomes. In this context, the role of microRNAs (miRNAs) – important epigenetic regulators of gene expression – in regulating mammalian immune systems is increasingly well recognised. However, the expression dynamics of miRNAs, and that of their isoforms, in response to infection remains largely unexplored. Here, we characterized the genome-wide miRNA transcriptional resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 101 publications
8
79
0
2
Order By: Relevance
“…The lncRNAs expressed in response to TLR stimulation might belong to a core response to fine tune immune function as described for microRNAs (Siddle et al, 2015). If there are specific lncRNA candidates manipulated by bacterial effector proteins or individual virulence factors needs to be in the focus of further investigations.…”
Section: Functional and Mechanistic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNAs expressed in response to TLR stimulation might belong to a core response to fine tune immune function as described for microRNAs (Siddle et al, 2015). If there are specific lncRNA candidates manipulated by bacterial effector proteins or individual virulence factors needs to be in the focus of further investigations.…”
Section: Functional and Mechanistic Studiesmentioning
confidence: 99%
“…In case of miRNAs it was shown that a core temporal miRNA expression pattern is induced in response to infection, shared across different bacterial species. In addition, pathogen-specific miRNAs were identified reflecting the mechanism by which certain pathogens interfere with the host response to infection (Siddle et al, 2015). Studies comparing the lncRNA expression in response to different pathogens possessing different virulence mechanisms are missing.…”
Section: Conclusion/outlookmentioning
confidence: 99%
“…A recent analysis of the miRNAs expressed in dendritic cells in response to six different bacteria has revealed a core temporal response to infection comprising 49 miRNAs that may play an essential role in response to infection, in addition to subtle variability for each bacterium, that can be considered as a specific signature [29] (Fig 1a). Moreover, infection can induce a switch in the relative abundance of mature miRNAs deriving from the 5' and 3' arms of the precursor (a process described as "arm-switching", [30] , Fig 1b), and changes the proportion of miRNA variants (isomiRs, Fig 1c).…”
Section: Discovery Of Microrna Response Against Pathogensmentioning
confidence: 99%
“…Moreover, infection can induce a switch in the relative abundance of mature miRNAs deriving from the 5' and 3' arms of the precursor (a process described as "arm-switching", [30] , Fig 1b), and changes the proportion of miRNA variants (isomiRs, Fig 1c). Such variability in miRNA identity is thought to affect their regulatory potential, but this aspect deserves more investigations [29].…”
Section: Discovery Of Microrna Response Against Pathogensmentioning
confidence: 99%
“…These forms of heterogeneity in miRNAs sequence and length may affect the selecting target, miRNAs steadiness, or loading into the RNA-induced silencing complex (RISC) (2), miRNA half-life, subcellular localization (1). According to Cloonan and etal, isomiRs in biological and functional pathway such as gene targeting collaborate with canonical miRNAs (3) , therefore, suggested every changes in isomiRs proportions have functional effect on gene regulation (4). IsomiRs can be the extension of the miRNAs, which will contribute to flexible and powerful microRNAs are regulatory non-coding RNA molecules that containing about 18-24 nucleotides which involved in critical steps of many cellular processes, specifically gene expression, therefore, their deregulation can lead to human tumorigenesis.…”
mentioning
confidence: 99%